Forehead Reduction Surgery with Hairline Advancement - Espinosa, Jorge; Solís, Luis; Cobo, Roxana; Heredia, Nicolas; Puerta, Mauricio; Corredor, Diego; Fonseca, Carol (Facial Plastic Surgery, 2024)
Hairline reduction surgery, also known as aesthetic forehead reduction, is a surgical procedure that aims to reduce the upper facial third and improve facial harmony. This article describes the anatomy of hairline advancement surgery and the surgical technique used by the author. The study included 21 patients from 2019 to 2023, and the forehead reduction length was on average 22.48 ± 2.64 mm. The most common complaint was hypoesthesia of the scalp, present in 100% of patients, resolving in all cases by 2 months after surgery. Forehead reduction surgery is among the procedures that provide more satisfaction to patients due to the great changes that it can achieve.
Keywords: scalp advancement; forehead reduction; hairline lowering